A new Encephalarteae trunk (Cycadales) from the Cretaceous of Patagonia (Mata Amarilla Formation, Austral Basin), Argentina. (April 2017) - Martínez, L.C.A.; Iglesias, A.; Artabe, A.E.; Varela, A.N.; Apesteguía, S.
Abstract: The cycads are remnants of a flora that dominated the terrestrial ecosystems across the Mesozoic Era. The stem record of fossil cycads is scanty, with seventeen genera described around the world. From them, eight come from Argentina (Triassic to Paleogene strata), and actually six from the Cretaceous of Patagonia. In this research, we present a new fossil trunk of cycad from Upper Cretaceous beds of Patagonia. The good preservation of the permineralized stem allows to make detailed descriptions and comparisons and, accordingly, support the erection of a new taxon, Zamuneria amyla gen. et sp. nov. This new taxon possesses characters that fit with the Encephalarteae (e.g., columnar stem with persistent leaf bases and cataphylls, a wide pith, medullary vascular bundles, mucilage canals and idioblasts, a polyxylic vascular cylinder). Some features present in Zamuneria are discussed, such as the great development of parenchyma tissues with a marked amount of specialized cells (idioblasts), probably related with some protective function. Furthermore, the presence of cycads during the deposition of the Mata Amarilla Formation allows inferring climatic conditions, as well as a greater diversity of Encephalarteae in South America reinforces the endemic conditions for this group for the Cretaceous of southern continents. Highlights: Manoxylic fossil wood from Early Cretaceous of Patagonia was studied. The fossil wood studied corresponds to a new genus of Cycadales. The new taxon shares features with extant members of Encephalarteae tribe (Zamiaceae). An early diversification of Encephalarteae from the Lower Cretaceous is suggested. This record proposes a warm climate in Lower Cretaceous of Mata Amarilla Formation.